Breast hibernomas: Questioning the embryological origin?. Issue 2 (8th August 2017) - Benn, Carol‐Ann; Coetzee, Kirsten; Rayne, Sarah
Abstract: This paper aims to review the concept of hibernomas, with focus on their occurrence, in the breast. It will make reference to a specific case from the Helen Joseph Hospital's Breast Clinic situated in Johannesburg, South Africa. We describe the clinical, radiological and pathological findings in a patient as well as the final diagnosis and treatment (in the form of surgery). This report emphasizes the distinguishable features of hibernomas, and gives guidance as to the surgical approach in large hibernomas stressing the ease of achieving cosmesis without major oncoplastic techniques. More specifically, discussion as whether these rapidly growing, nonrecurring, usually encapsulated growths consisting of brown fat tissue similar to that found in hibernating animals arise from the breast or the underlying muscle is considered.